Rang and Dale's : pharmacology - Dale, M. M.; Flower, R. J. [ (Rod J.)] , 1945-; Rang, H. P.; Ritter, J.M
Medical knowledge is constantly changing. Standard safety precautions must be followed, but as new research and cinical experience broaden our knowledge, changes in treatment and drug therapy may become necessary or appropriate. Readers are advised to check the most current product information provided by the manufacturer of each drug to be administered to verify the recommended dose, the method and duration of administration, and contraindcations. It is the responsibility of the practitioner, relying on experience and knowledge of the patient, to determine dosages and the best treatment for each individual patient. Neither the Publisher nor the editors assume any liability for any injury and/or damage to persons or property arising from this publication.